Nāṭyaśāstradiśā rasatattva-paramparāyāḥ samīkṣaṇam - Kusuma Reddy, K. (Caukhambhā Saṃskr̥ta Bhavana granthamālā ;, 2008)
On the theories of aesthetic experience Rasas in Sanskrit dramaturgy with special reference to Nāṭyaśāstra of Bharatamuni.